Thallium(III) p-tosylate-mediated oxidative [1,2] rearrangement of 2-naphthyl and 2-heteroarylchromanones - Kurapati, Chidvilas; Muthukrishnan, Murugan; Singh, V. Om; Gundla, Rambabu (Journal of Heterocyclic Chemistry, 2022)
A practical and effective approach towards the synthesis of 3-heteroaryl-4H-chromen-4-ones by the oxidative [1,2] rearrangement of the respective 2-heteroaryl chroman-4-ones using thallium(III) p-tosylate is presented. The oxidative rearrangement of alpha- and beta-naphthyl and thiophene substituents behaves like aryl groups; However, pyridyl substituents gave only dehydrogenated products.